Electronic Device for Satellite Backup of Automatic Vehicle Location Equipment Using the Iridium Network (2020)
Context: This paper presents the design and development of an electronic device that operates as a satellite backup channel for automatic vehicle location (AVL) equipment, whose only communication channel is the cellular network. Method: The design, manufacture and assembly of the hardware followed 4 phases, and it was aligned with the IPC 2221 standard. This allowed improving the design experience and guaranteed the correct electrical operation in the final product. Results: The information sent by the developed device corresponds to the data generated by the AVL device, which indicates that the information processing was correctly designed. Additionally, it was possible to obtain a functional and versatile device in which the blocks were correctly integrated; its firmware was designed to receive future updates that improved and expanded its capacity and compatibility with other devices. Conclusions: The final product, which works with the Iridium network, seeks to satisfy the technological requirements of the freight transport sector in Colombia with a low-cost, versatile, and easily integrated solution. The implementation of this type of technologies expands the capacity of tracking mobile assets, even in places where there is no cellular network coverage.